2020
DOI: 10.1186/s12903-020-01270-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 transmission risk and protective protocols in dentistry: a systematic review

Abstract: Background Among several potential transmission sources in the spreading of the COVID-19, dental services have received a high volume of attention. Several reports, papers, guidelines, and suggestions have been released on how this infection could be transmitted through dental services and what should be done. This study aimed to review the guidelines in order to develop a practical feasibility protocol for the re-opening of dental clinics and the reorientation of dental services. Methods This study systemat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
159
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 44 publications
2
159
0
14
Order By: Relevance
“…It would also help to avoid nosocomial infections due to admission for elective procedures. Although such recommendations have been made by several studies ( 13 , 14 , 15 , 16 ) and from governmental agencies in different countries, ( 4 , 17 ) the Brazilian government delayed adopting the WHO determinations for self-isolation, border closures, limitations on non-essential elective services in the public health system, and extensive testing for all suspected cases. As of DATE, the spread of COVID-19 in Brazil has killed more than 215,000 and infected more than 8 million Brazilians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would also help to avoid nosocomial infections due to admission for elective procedures. Although such recommendations have been made by several studies ( 13 , 14 , 15 , 16 ) and from governmental agencies in different countries, ( 4 , 17 ) the Brazilian government delayed adopting the WHO determinations for self-isolation, border closures, limitations on non-essential elective services in the public health system, and extensive testing for all suspected cases. As of DATE, the spread of COVID-19 in Brazil has killed more than 215,000 and infected more than 8 million Brazilians.…”
Section: Introductionmentioning
confidence: 99%
“…Although the available evidence has not demonstrated a clear and direct relationship between dental treatment and transmission of COVID-19, there is clearly the potential for transmission since some dental procedures generate aerosols containing salivary droplets, which is how SARS-CoV-2 is transmitted ( 13 , 16 ). However, the suspension of non-urgent elective procedures may be seen as a relevant side effect of the measures adopted to reduce COVID-19 contamination, since the reduction of such treatments might result in significant oral health deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients simultaneously present in the office was reduced as far as possible, and sufficient distance had to be ensured, for example a one meter distance between seats in the waiting area. Magazines and demonstration models in the waiting room were removed as their proper disinfection could not be guaranteed [ 6 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of aerosol-producing actions like ultrasonic scaling, restorative procedures or bracket/attachment removal with high speed handpieces decreases the risk of air-borne transmission [ 14 ]. If aerosol generating procedures cannot be avoided, high-volume salivary ejectors are necessary [ 15 ]. The use of rubber dams reduces aerosolized particles by 70% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study on COVID-19 infection in the dental setting reported nine confirmed cases among the dental team in the School and Hospital of Stomatology, Wuhan University, Wuhan, China. [ 31 ] It was suggested in a systematic review of 9 studies that assessed the transmission of COVID-19 in the dental clinic that there is a potential for transmission, through saliva, bodily fluids, aerosols, contaminated instruments, and surfaces[ 32 ] Nonetheless, one cannot underestimate infection control measures being second nature to most dentists, who routinely wear gloves and a mask, often with eye protection, when treating patients. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%